The Existence of the Land Bank Agency within the Framework of State Control Rights - Intan Juwitasari; Casanova Sitohang (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Land plays a strategic role in supporting development, investment, and public welfare; however, persistent challenges such as land disputes, unequal ownership, and limited land availability continue to hinder the realization of equitable land governance. These conditions have prompted the establishment of the Land Bank Agency as a national instrument for land management. This study aims to analyze the position of the Land Bank Agency within the Indonesian land law system and to examine the philosophical, juridical, and constitutional foundations underlying its establishment as an institution implementing the State’s Right to Control over land. The research employs a normative legal method using statutory, conceptual, and historical approaches through the examination of primary, secondary, and tertiary legal materials. The findings indicate that the Land Bank Agency constitutes a sui generis legal entity authorized to perform land planning, acquisition, procurement, management, utilization, and distribution functions for the purposes of public interest, agrarian reform, economic equity, and national development. The study concludes that the Land Bank Agency possesses strong constitutional and legal legitimacy as an instrument of state land governance. Nevertheless, strengthening institutional oversight, transparency, accountability, and the harmonization of authority among relevant institutions remains essential to ensure legal certainty, justice, and sustainable land management.